Temporary improvement of cognitive and behavioral scales for Dementia elderly by Shiritori word game with a dialogue robot: A pilot study - Sugiyama, Hiroaki; Nakamura, Kenji (Frontiers in Robotics and AI, 2022)
Communication therapies based on conversations with caregivers, such as reminiscence therapy and music therapy, have been proposed to delay the progression of dementia. Although these therapies have been reported to improve the cognitive and behavioral functions of elderly people suffering from dementia, caregivers do not have enough time to spend on administering such communication therapies, especially in Japan where the workforce of caregivers is inadequate. Consequently, the progression of dementia in the elderly and the accompanying increased burden on caregivers has become a social problem. While the automation of communication therapy using robots and virtual agents has been proposed, the accuracy of both speech recognition and dialogue control is still insufficient to improve the cognitive and behavioral functions of the dementia elderly. In this study, we examine the effect of a Japanese word-chain game (Shiritori game) with an interactive robot and that of music listening on the maintenance and improvement of cognitive and behavioral scales [Mini-Mental State Examination (MMSE) and Dementia Behavior Disturbance scale (DBD)] of the dementia elderly. These activities can provide linguistic and phonetic stimuli, and they are simpler to implement than conventional daily conversation. The results of our Wizard-of-Oz-based experiments show that the cognitive and behavioral function scores of the elderly who periodically played the Shiritori game with an interactive robot were significantly improved over the elderly in a control group. On the other hand, no such effect was observed with the music listening stimuli. Our further experiments showed that, in the Shiritori intervention group, there was a ceiling on the increase in MMSE. The lower the MMSE before participating in the experiment, the greater the increase. Furthermore, greater improvement in DBD was observed when the participants actively played the Shiritori game. Since the Shiritori game is relatively easy to automate, our findings show the potential benefits of automating dementia therapies to maintain cognitive and behavioral functions.